The Development of Pisa-Based Buffer Solutions and Its Application Using the Kahoot Platform - Abdul Gani; Muhammad Nazar; Qurratun ‘Akyun (Jurnal Penelitian Pendidikan IPA, 2022)
An innovation in media technology that can be used in the field of education is Kahoot. Kahoot is an online application in the form of a platform. Kahoot app as a learning technology platform can combine the implementation of interactive quizzes. The problems that exist in SMA Negeri 3 Banda Aceh for students in learning chemistry are about understanding concepts that are still lacking. For this reason, it is necessary to conduct research on "Development of Pisa-Based Buffer Solution Material Problems and Its Application Using the Kahoot Platform". The purpose of this study is developing an interactive quiz media based on Kahoot educational games on buffer solution, to describe teacher responses to the use of interactive quiz media based on Kahoot, and to describe students responses to the use of interactive quiz media based on Kahoot. This study uses a quantitative approach with the type of Research and Development (R&D) research using the ADDIE model. The result of the research is that the feasibility of interactive quiz media based on the educational game Kahoot on the material of the buffer solution carried out by the lecturer of the Department of Chemistry Education still needs a feasibility test through one stage of improvement. The teacher's response to the four indicators received a positive response. Students' responses to the use of the quiz media also received positive responses from students, besides that it also increased student learning outcomes and did not cause students to feel monotonous